2022
DOI: 10.3389/fpsyt.2022.999089
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, parenting, mental disorders, life stressors and help-seeking behavior of Asian adolescent suicide attempters: A case control study

Abstract: PurposeThe need to elucidate risk factors for adolescent suicide is urgent, as suicide consistently ranks among the top causes of death globally. Understanding suicide risk factors could inform more effective interventions. Previous studies have identified certain risk factors associated with suicide, but there is a paucity of research among adolescent and multi-ethnic Asian populations.Materials and methodsThis case-control study sampled 13-to-19-year-old Asian adolescents who had attempted suicide (N = 60) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…19 Research has indicated that the parenting style and life stressors experienced by college students have a significant impact on their negative mental health behaviors, such as suicide. 21 Our study aims to investigate whether different parenting styles may influence individuals' ability to adapt to life events and potentially lead to depressive symptoms.…”
Section: Epidemiological Characteristics Of Depressive Symptomsmentioning
confidence: 99%
“…19 Research has indicated that the parenting style and life stressors experienced by college students have a significant impact on their negative mental health behaviors, such as suicide. 21 Our study aims to investigate whether different parenting styles may influence individuals' ability to adapt to life events and potentially lead to depressive symptoms.…”
Section: Epidemiological Characteristics Of Depressive Symptomsmentioning
confidence: 99%
“…Heikkinen et al looked into the life circumstances that the wives of the suicides went through before committing suicide and found that an aver-age of 2.6 life events were encountered by 85% of the patients in the three months prior to their suicide (18). The most frequent occurrences in people's lives were health issues, family strife, and challenges at work, the top three life events that contributed to suicide were marital discord, financial hardships, and facing discrimination (19)(20)(21)(22).…”
Section: Life Eventsmentioning
confidence: 99%